Genesis of MgCl2‐based Ziegler‐Natta Catalysts as Probed with Operando Spectroscopy. Issue 20 (3rd August 2018) - Piovano, Alessandro; Pletcher, Paul; Velthoen, Marjolein E. Z.; Zanoni, Silvia; Chung, Sang‐Ho; Bossers, Koen; Jongkind, Maarten K.; Fiore, Gianluca; Groppo, Elena; Weckhuysen, Bert M.
Abstract: Z iegler‐Natta catalysts for olefin polymerization are intrinsically complex multi‐component systems. The genesis of the active sites involves several simultaneous and sequential steps, making the individual steps and interconnections difficult to be unraveled in an unambiguous manner. In this work, we combine X‐ray diffraction and spectroscopy to probe each step of the birth and life of a MgCl2 ‐based Ziegler‐Natta catalyst, namely the formation of high surface area MgCl2 by dealcoholation of an alcoholate precursor, the TiCl4 grafting, and the subsequent activation by triethylaluminum as co‐catalyst. The so‐prepared catalyst was tested towards ethylene polymerization, leading to the production of mainly crystalline high‐density polyethylene. The use of operando characterization techniques allowed probing the transient details that are difficult to be dissected in the aftermath, but can radically affect the overall catalytic process. Abstract : Operando X‐ray diffraction and spectroscopy techniques are applied to obtain information about the structure, electronic properties, and functional groups of some Ziegler‐Natta catalysts. Each step of the synthesis is singly characterized: the activation of the MgCl2 support material, the formation of the pre‐catalyst by TiCl4 chemisorption, and the activation with triethylaluminum. The so‐formed catalyst is very active to ethylene polymerization in the gas phase at room temperature.